Pola Asuh Siswa Di Asrama Pondok Pesantren Sekolah Menengah Kejuruan - Yuniarsih Sri Rahayu (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2020)
The purpose of this research to describe the parenting that is implemented in boarding schools, including authoritarian parenting, permissive parenting, democratic parenting. This research is a quantitative descriptive study. Data collection techniques used questionnaires and documentation. The research instrument was a questionnaire. Data analysis techniques used quantitative descriptive analysis by calculating the mean, median, mode, and standard deviation. The results showed that parenting in Islamic boarding schools was in the sufficient category with a relative frequency of 62%. Parenting applied in Islamic boarding schools has three indicators, namely authoritarian parenting, permissive parenting, democratic parenting with the following conclusions. Authoritarian parenting in the sufficient category with a relative frequency of 62%. Democratic parenting in the category with a relative frequency of 78%. Permissive parenting category is sufficient with a relative frequency of 54%. That is, all three parenting have an impact in every application.